Gender Discrimination and Its Impacts in Macro-Economic Development - Shrestha, Savitri (KMC Research Journal, 2019)
Gender refers to the complex social construction of men’s and women’s identities. Sex and gender are different. The biological or physical construction is sex, which is created by nature. Gender is  purely a social construct.Gender Equality is a concept that is yet to be materialized. Around the world different individuals and groups of people are marginalized and discriminated on the basis of various factors, but discrimination against women is universal. Due to this, women are not able to use their full potential or assert their rights to live healthy life, and it has a deep impact in economic development.Gender equality is not only matter of human right but also basic of economic development. Gender inequality is a severe obstacle to socio-economic development, human capital development and income generation. Gender inequality is harmful to long term development and growth. Unequal gender will never alone be sufficient for poverty reduction and economic development.Gender discrimination not only affects females but males as well. The discriminatory practices do not only affect individuals but national economy and world economy as a whole. Due to stereotypical division of work most men are over loaded with economic duties, while women are being limited to household works only. Fifty per cent of the world population is over-loaded with economic duties, while fifty per cent of the brain is underutilized. The economic value of the household work which is done by females is not calculated and reflected in a country’s economy. This devalues the effort and work done by females and also is loss for the national economy. Education and development goes together, for a better balance of gender, educational equality is must. Education is key factor to promote human capital, which ensures economic growth. Formal education, trainings, study programs improves the capacity of individuals to live a decent life, which is the basic of development. Gender will never alone be sufficient for development.Gender equality is not only matter of human right but also basis of economic development.